2021
DOI: 10.1161/hypertensionaha.121.17316
|View full text |Cite
|
Sign up to set email alerts
|

Stage III Hypertension in Patients After mRNA-Based SARS-CoV-2 Vaccination

Abstract: e57 Meylan et al Post-COVID-19 Vaccine Hypertensionexplicitly as an adverse event in both safety/immunogenicity trials. However, both phase I/II and III clinical trials for the mRNA vaccines included predominantly younger populations with a mean and median age of 31 and 52 years for the BNT162b2 vaccine 4 and 31 and 51 for the mRNA-1273 vaccine. 5 Although more data are needed to understand the extent and the mechanism of hypertension after mRNA-based vaccination, our data indicate that in elderly patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 5 publications
(5 reference statements)
3
77
0
1
Order By: Relevance
“…These findings extend those by Meylan et al [4] who described 9 patients with stage III hypertension after the Pfizer/BioNTech vaccine. In the present study we had the opportunity to investigate self-measured home BP before and after vaccination.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These findings extend those by Meylan et al [4] who described 9 patients with stage III hypertension after the Pfizer/BioNTech vaccine. In the present study we had the opportunity to investigate self-measured home BP before and after vaccination.…”
supporting
confidence: 90%
“…However, some concerns have been raised regarding the safety of SARS-CoV-2 vaccines, largely based on reports of serious thromboembolic events after vaccination [1] . There are also anecdotal data of systemic reactions to vaccination including hypertension [4] and tachycardia [5] .…”
mentioning
confidence: 99%
“…Meylan et al, in their study, reported a case series of nine patients with stage III hypertension after mRNA-Based COVID-19 vaccination; later, it was found that eight out of nine patients had a history of hypertension and were on medication. 53 As reporting of adverse events considers any events post-administration of a drug or vaccines, causality assessment of all the reported adverse events must be done to conclude. Moreover, time from exposure to adverse events needs to be analyzed to determine whether a particular event is causally associated with the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fluctuation of BP is not considered as part of the AEFI, these observations can significantly affect subjects with co-morbidities. This concern seems valid as there is a case series recently published on eight vaccinees who experience elevated high BP after receiving the vaccine 7 . This observation is a valid concern and warrants further investigation on the relationship between vaccine and BP levels.…”
Section: Introductionmentioning
confidence: 96%